Clinical Outcome Following Oral Potentially Malignant Disorder Treatment: A 100 Patient Cohort Study - A. Diajil; C. M. Robinson; P. Sloan; P. J. Thomson (International Journal of Dentistry)
Oral potentially malignant disorders (PMDs) are at risk of transforming to invasive squamous cell carcinoma (SCC), but controversy exists over their management and the precise role of interventional treatment. In this study, a cohort of 100 patients presenting with new, single oral dysplastic PMD lesions were followed for up to 10 years following laser excision. PMDs presented primarily as homogeneous leukoplakias on floor of mouth and ventrolateral tongue sites and showed mainly high-grade dysplasia following analysis of excision specimens. Sixty-two patients were disease-free at the time of the most recent followup, whilst 17 experienced same site PMD recurrence, 14 developed further PMDs at new sites, 5 underwent same site malignant transformation, and 2 developed SCC at new oral sites. Whilst laser excision is an effective therapeutic tool in PMD management, prolonged patient followup and active mucosal surveillance together with clear definitions of clinical outcomes are all essential prerequisites for successful interventional management. Multicentre, prospective, and randomised trials of PMD treatment intervention are urgently required to determine optimal management strategies.